Implikasi Biaya Kualitas Terhadap Produk Rusak Pada Produk Cake Home Industri - Nasyaroeka, Jhon; Yuniastuti, Rina Milyati; Lestari, Fransiska Wahyu (Lembaga Penelitian, dan Pengabdian Kepada Masyarakat (LPPM) STIE GENTIARAS Bandar Lampung dan berkolaborasi dengan Ikatan Akuntan Indonesia Kompartemen Akuntan Pendidik (IAI KAPd), 2023)
Quality cost is the costs to prevent defective products that do not comply with the company's standard criteria. This research was conducted because there were products that did not comply with the company standard, especially products in the home industry. For this reason, the research aims to analyze the implications of quality costs on defective products by looking at two quality costs, that is prevention costs and assessment costs. Products said as defective products in this research are damage or failed products. The object of this research was carried out in the home food industry business of making onion cakes. The method in this research is descriptive quantitative analysis. The statistical tests were multiple linear regression, simultaneous test and t test. The result of the F test shows that prevention costs and assessment costs affect the defective products simultaneously. The t test result shows that prevention cost has an effect towards defective products and also assessment costs have an effect towards defective products. This research has implications for home industry products to reduce the quality costs so that no more defective products produced.